Dinâmica populacional e variabilidade genética da mosca branca Bemisia tabaci (Gennadius, 1889) biótipo B (Hemiptera: Aleyrodidae) em cultivos olerícolas em São Luís – MA - Silva, Maria Cleoneide da (2006)
The whitefly Bemisia tabaci (Gennadius, 1889) is an important pest of world-wide the agricultural production. The population dynamics and the genetic variability are indispensable knowledge as principle of the integrated management of this pest. In the Maranhão it does not exist works on the genetic variability of the populations of this insect. The present work had as objective to evaluate the population dynamics of B. tabaci through the direct counting of immature stage on leaves and of the adults in adhesive yellow traps (10cm x 30cm) during two phenologics cycles in cultures of the okra, beans and cucumber and to molecularly characterize populations of collected B. tabaci in okra, beans and green pepper cultures through molecular markers RAPD, in polos of agricultural production of São Luís - MA. For the sampling of the study of the population dynamics 10% of the area of each culture were used, where it collected leaves of the apical, middle and bottom parts for the counting of immature stage biweekly. The traps, for the counting of the adults, had been placed in proportional amounts for each 300m2 in the interior of the cultivated areas, being analyzed weekly. For the determination of the vertical distribution of the nymphs in the studied cultures, an index of nymphs/leaf was determined, for each part of the plant and each one of the four ínstares. The indices gotten had been submitted to the variance analysis and the averages compared for the test of Tukey, to the level of 5% of probability, were used for this, the Estat program v.2. For the comparison of the variation of the mean density in each immature stage in the two phenologics cycles, test T to the level of 5% of probability was used. With regard to the population fluctuation of the adults, it was used it adds it of the averages biweekly and one compared with the biweekly average of the temperature and precipitation. For the molecular characterization they had been analyzed, through the technique of RAPD, using itself 12 primers, females of whitefly of nine populations, collected in okra cultures, beans and green pepper and compared with biotype B of B. tabaci proceeding from the Embrapa (Brasilia-DF). 96 molecular markers RAPD had been produced and through program STATISTIC version 6.0, these markers had generated a dendrogram. Through the gotten results, it was concluded that the vertical distribution of the nymphs of the white fly occurs of sufficiently linear form, having predominance of the nymphs of first instar in youngest leaves e of other stages in the inferior terços of the plant. It was observed that during phenologic cycle I, it had minor incidence of nymphs and adults when compared with fenológico cycle II, period where the lesser pluviometric indices had been evidenced. Primers had produced standards specific bands, who had allowed to confirm that the evaluated specimens belong to the group of biotype B of B. tabaci. The populations of the culture of the okra, the beans and the green pepper had presented a genetic similarity from 80%, 76% and 45%, respectively, when compared with biotype B. The results had also shown that it occurred lesser selective pressure with the population of whitefly collected in the culture of the green pepper and minor genetic variability with the populations of whitefly collected in the cultures of the okra and beans.